Waqf-Based Entrepreneurship Direct Financing Model: Potential and Challenges - Rindawati Maulina; Wawan Dhewanto; Taufik Faturohman (Research Synergy Foundation, 2023)
Continuous effort to strengthen the integration of Islamic commercial finance and Islamic social finance becomes salient. The use of Waqf (Islamic endowment) assets for various sectors and infrastructure development, which is supported by technological advancement, can also help the economy recover, particularly in the current economic downturn caused by the Covid-19 pandemic. Unfortunately, Waqf-based entrepreneurs who contribute significantly to the sustainability of Waqf benefits, continue to face significant difficulties in obtaining capital for the development of Waqf assets. Based on a review of the existing literature and findings from the case study through in-depth interviews with selected respondents, the study aims to propose a direct financing model for Waqf -based entrepreneurs by empowering affluent Muslim potentials through Islamic banks. There are five (5) fundamental criteria considered as strategic for the integration model to successfully empower Waqf-based entrepreneurship in Indonesia, namely continuous literacy and education on contemporary Waqf, the transformation of regulatory and management transparency, improvement of the professionalism and business capacity of the Waqf-based entrepreneurs, synergy, and collaboration among stakeholders, and integrated and reliable infrastructure.